Transient lightning response of grounding grids in a horizontal, multilayered soil model that considers soil ionization effects with time‐domain quasi‐static complex images. (22nd June 2018) - Li, Zhong‐Xin; Rao, Shao‐Wei
Abstract: A novel mathematical model is proposed that can accurately calculate the lightning current distribution and lightning impulse response of a grounding horizontal grid with a vertical rod embedded in a horizontal, multilayered earth model, under the consideration of soil‐ionization effects. To improve the computational efficiency, a quasi‐static complex image method and the closed form of the time‐domain Green's function were introduced into the model.